2010
DOI: 10.1016/j.matdes.2010.01.051
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic properties of multi-walled carbon nanotube/epoxy composites using two different curing cycles

Abstract: Along with carbon nanotubes (CNT) morphology, impurity, and functionalization, polymer curing cycle is another important factor in determining the mechanical properties of the CNT/polymer composite samples. This work investigates the effect of two different curing cycles on mechanical and thermo-mechanical properties of the nanotube in the composite in order to optimize the curing condition in term of time and temperature. Nanocomposite samples were prepared by mixing multi-wall carbon nanotubes with epoxy res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
41
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(44 citation statements)
references
References 25 publications
3
41
0
Order By: Relevance
“…Similar results have been published for CNTs modified epoxies, where it was shown that the dispersion conditions are of key importance to obtain improvements in both toughness and thermomechanical properties [11][12][13]. Only a small weight fraction of CNTs has been reported to improve the mechanical, thermal and electrical properties when dispersed in the matrix of typical aerospace composites [14][15][16][17].…”
Section: Introductionsupporting
confidence: 78%
“…Similar results have been published for CNTs modified epoxies, where it was shown that the dispersion conditions are of key importance to obtain improvements in both toughness and thermomechanical properties [11][12][13]. Only a small weight fraction of CNTs has been reported to improve the mechanical, thermal and electrical properties when dispersed in the matrix of typical aerospace composites [14][15][16][17].…”
Section: Introductionsupporting
confidence: 78%
“…It is noted that the applicability of the SHPB technique needs to be examined carefully before reliable dynamic experimental data can be produced [17]. Recent modifications on the SHPB apparatus have been done for testing soft materials with valid testing conditions [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, they possess great potential to reinforce high performance composites with wide structural applications [4,5]. Significant research attempts have sought to incorporate CNTs into fiber reinforced composites in order to improve the matrix [6,7] or fiber-matrix interfacial characteristics [8,9].…”
Section: Introductionmentioning
confidence: 99%